Quality of life among medical students during Covid-19 pandemic - Razman, Amalia Izzati; Nor Azlan, Nur Khairunnisa; Shaik Mohd Nizam, Nur Alia Iman; Anuar, Muhammad Ashraf Fithri; Abdullah, Muhammad Haikal; Ahmad Ashhar, Muhammad Ikmal Arif; Mohamad, Mohammad Muaz; Shahrir, Shahida Athirah; Johari, Muhammad Luqman ‘Afif; Zulkifli, Ahmad Najmi Abid; Zamani, Muhammad Razin; Azani, Muhammad Adam; et al. (2021)
Medicine has a well-known reputation for being among the toughest courses to enrol in once a student step into college or university. Given the mounting pressure to excel in a high stake learning environment, undeniably their quality of life could be affected. With the added challenge of navigating online learning during a pandemic, the students’ well-being has become an issue of great concern. Therefore, this study aimed to evaluate the quality of life among preclinical medical students of International Islamic University Malaysia during COVID-19.